2023
DOI: 10.3389/fpls.2023.1201805
|View full text |Cite
|
Sign up to set email alerts
|

Ligand recognition and signal transduction by lectin receptor-like kinases in plant immunity

Abstract: Lectin receptor-like kinases (LecRKs) locate on the cell membrane and play diverse roles in perceiving environmental factors in higher plants. Studies have demonstrated that LecRKs are involved in plant development and response to abiotic and biotic stresses. In this review, we summarize the identified ligands of LecRKs in Arabidopsis, including extracellular purine (eATP), extracellular pyridine (eNAD+), extracellular NAD+ phosphate (eNADP+) and extracellular fatty acids (such as 3-hydroxydecanoic acid). We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 142 publications
0
2
0
Order By: Relevance
“…Our findings highlight the importance of the putative IDR in the extended C terminus of P2K1 in regulating eATP signaling, especially in the eATP-induced regulation of primary root growth. Additionally, our results suggest a critical role for eATP and P2K1 in regulating ROS and cell wall integrity in the primary root meristem, which are essential for plant growth and stress adaptation [57][58][59][60][61][62][63]. This study also provides a framework for generating other truncated RK variants based on IDRs that can help further unravel the functional significance of the C terminus in other receptor proteins.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings highlight the importance of the putative IDR in the extended C terminus of P2K1 in regulating eATP signaling, especially in the eATP-induced regulation of primary root growth. Additionally, our results suggest a critical role for eATP and P2K1 in regulating ROS and cell wall integrity in the primary root meristem, which are essential for plant growth and stress adaptation [57][58][59][60][61][62][63]. This study also provides a framework for generating other truncated RK variants based on IDRs that can help further unravel the functional significance of the C terminus in other receptor proteins.…”
Section: Discussionmentioning
confidence: 98%
“…Our study showed that MuLRR-RLK protein structure has a high homology to other LRR-RLK proteins ( Figure 5 ), indicating that it might have similar biological functions as other LRR-RLK proteins in the same subfamilies. It was reported that LRR-RLKs play vital roles in plant growth, development, and the responses to environmental stress, and some LRR-RLKs are associated with plant resistance to bacterial and fungal pathogen invasion [ 63 , 64 , 65 ]. However, to our knowledge, this is the first report that LRR-RLK genes are associated with the response to phytoplasma infection.…”
Section: Discussionmentioning
confidence: 99%